2022
DOI: 10.1021/acsnano.2c01286
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-Assisted Low-Thermal-Budget-Driven α-InGaZnO Thin Films for High-Performance Transistors and Logic Circuits

Abstract: Developing a low-temperature fabrication strategy of an amorphous InGaZnO (α-IGZO) channel layer is a prerequisite for high-performance oxide-based thin film transistor (TFT) flexible device applications. Herein, an ultraviolet-assisted oxygen ambient rapid thermal annealing method (UV-ORTA), which combines ultraviolet irradiation with rapid annealing treatment in an oxygen atmosphere, was proposed to realize the achievement of high-performance α-IGZO TFTs at low temperature. Experimental results have confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 54 publications
0
39
0
Order By: Relevance
“…Recently, the supreme properties of O/S have gained tremendous attention as a next-generation channel material in 3D DRAM, NAND, and M3D to meet the never-ending Moore’s law in the intelligent semiconductor chips. For a semiconductor application, the conventional physical vapor deposition (PVD) process cannot satisfy the stringent requirements such as conformal deposition and accurate thickness controllability on 3D nanoscaled structure, even though most of the work on O/S TFTs, until now, has been focused on the PVD route. As an alternative approach, the atomic layer deposition (ALD) technique can provide good conformality and accurate control of the composition thickness on the basis of its unique self-limiting growth behavior . These advantages enable the O/S channel layer to be embedded in complex three-dimensional (3D) device structures, such as FinFET, gate-all-around (GAA) transistor, 3D NAND devices, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the supreme properties of O/S have gained tremendous attention as a next-generation channel material in 3D DRAM, NAND, and M3D to meet the never-ending Moore’s law in the intelligent semiconductor chips. For a semiconductor application, the conventional physical vapor deposition (PVD) process cannot satisfy the stringent requirements such as conformal deposition and accurate thickness controllability on 3D nanoscaled structure, even though most of the work on O/S TFTs, until now, has been focused on the PVD route. As an alternative approach, the atomic layer deposition (ALD) technique can provide good conformality and accurate control of the composition thickness on the basis of its unique self-limiting growth behavior . These advantages enable the O/S channel layer to be embedded in complex three-dimensional (3D) device structures, such as FinFET, gate-all-around (GAA) transistor, 3D NAND devices, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the increase in the S.S. value in the Sn 5 device results from increased oxygen-related defects increasing N ss . Figure (c) compares the device performance in this work and previously reported devices, in terms of the S.S. and μ FE values. , Compared to devices in other reports, the Sn 3 device shows the best performance, with outstanding S.S. and reasonable μ FE values. In particular, the Sn 3 device has an extremely low S.S. (64.8 ± 1.9 mV/dec.…”
Section: Resultsmentioning
confidence: 64%
“…It can be observed that the local environment remains almost unchanged with increasing B doping concentrations. However, the In peak gradually shifts toward low binding energy, which is, on the one hand, due to due to the bonding strength of B-O (808 kJ/mol) being stronger than that of In-O (346 kJ/mol), and on the other hand because B doping can reduce oxygen vacancy-related defects, resulting in a denser atomic stacking and enhanced electron shielding between adjacent atoms [ 25 , 26 , 27 ]. Figure 3 c presents the XPS spectra of B 1s with different B contents.…”
Section: Resultsmentioning
confidence: 99%